2023
DOI: 10.1002/pc.27223
|View full text |Cite
|
Sign up to set email alerts
|

Bending property of novel 3D woven variable thickness composites: Experiment and finite element analysis

Abstract: Variable thickness composites are essential engineering materials which have been used in various high‐performance products. However, the commonly used variable thickness composites are mainly lamination, which is prone to delamination and reduce the overall performance under load. To solve this problem, 3D woven fabrics with integrity and continuous variable thickness have been designed and weaved on ordinary looms using basalt yarns. The resin‐based variable thickness composites have been prepared by vacuum‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Thus a multiscale FE model consisting of a mesoscopic deformed part and a macroscopic homogeneous part was considered. Referring to our previous work and considering the geometrical symmetry of the specimen, 35,36 a quarter macro–meso hybrid model is proposed to effectively balance the calculation accuracy and calculation efficiency 37,38 …”
Section: Modeling Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus a multiscale FE model consisting of a mesoscopic deformed part and a macroscopic homogeneous part was considered. Referring to our previous work and considering the geometrical symmetry of the specimen, 35,36 a quarter macro–meso hybrid model is proposed to effectively balance the calculation accuracy and calculation efficiency 37,38 …”
Section: Modeling Proceduresmentioning
confidence: 99%
“…Referring to our previous work and considering the geometrical symmetry of the specimen, 35,36 a quarter macro-meso hybrid model is proposed to effectively balance the calculation accuracy and calculation efficiency. 37,38 In this paper, the highly adaptable second-order tetrahedral cell (C3D10) was used to mesh the unit-cell model. To ensure the quality and reliability of the finite element simulation, three mesh densities (0.15, 0.2, and 0.25 mm) were selected for comparison.…”
Section: Statistical Analysis Of Crack Poresmentioning
confidence: 99%
“…55 A meso-finite element was used to analyze the damage performance of 3D woven tapered composites by Liu et al. 56 Due to the absence of a tapered finite element formulation adapted to study laminated plates with variable thickness in the literature, the present study introduces a novel approach for the dynamic analysis of thin and internally tapered laminated plates. Strain and stress fields are expressed per classical laminated plate theory (CLPT).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, numerous studies have been conducted to investigate their mechanical properties under various loads such as tension, 4 compression, 5 and bending. 6 Previous research has demonstrated that the compression behavior of 3D woven composites, which is essential for the reliability of load-bearing structures, is affected by both the preform structure and fiber content along the loading direction. 4,7,8 It is feasible to improve the compression strength by optimizing the fiber content.…”
Section: Introductionmentioning
confidence: 99%